Ranking public policy and administration graduate program, 1995-2016: an analysis and discussion - Frederickson, H. George; Stazyk, Edmund C. (2016)
In 1995, U.S. News and World Report (U.S. News) released its first ranking of public affairs master's degree programs. The rankings have been conducted every 3 years since and have grown in importance to public policy and public administration programs. This study considers the history and background of ranking public policy and administration graduate programs, the rationale used by U.S. News, and the methodology used by U.S. News. This is followed by a longitudinal analysis of these rankings from 1995 to 2016. Findings are presented in a conceptual framework of academic rankings using concepts of equilibrium, specialization, diffusion of innovations, and institutional isomorphism. The implications of this framework and the findings of our analysis are spelled out for public affairs deans, directors, and faculty seeking to improve their ranking as well as those seeking to hold on to their present rankings. - Reproduced.
Keywords: Public administration; Public policy